Odpowiedzi

Najlepsza Odpowiedź!
2009-12-20T12:36:25+01:00
A)a=[2,-3] b=[1+ k, m]

(-a)=b (lub a=-b, jak lepiej ci pasuje)
-xa=xb i -ya=yb itd robisz z wszystkimi:

-2=1+k
k=(-3)

-(-3)=m
m=3

k=(-3) ^ m=(3)
-------------------------------------
b)a=[k+1,2m] b =[2k,m +5]
a=(-b)
k+1=-2k
3k=-1
k= (-1/3)

2m=-m-5
3m=-5
m= (-5/3)
-------------------------------------
c)a=[k-5,4] b=[-3,3m-1]
(-a)=b
5-k=-3
-k=-8
k=8

-4=3m-1
3m=-3
m=(-1)
-------------------------------------
d)a=[k+m,k-m] b=[9,-15] <-- Tutaj będzie układ równań:
a=(-b)

{k+m=-9
{k-m=15

2k=6
k=3

m=-9-k
m=(-12)